THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND INTELLECTUAL CAPITAL ON FIRM VALUE WITH PROFITABILITY AS INTERVENING VARIABLE - Muthyah Ainunsary Mustafa; Cacik Rut Damayanti; Ferina Nurlaily (Universitas Semarang, 2020)
The purpose of this research is to examine the effect of Corporate Social Responsibility and Intellectual Capital on Firm Value with Profitability as Intervening Variable. The type of research is explanatory research with quantitative approach. The data analysis technique used are descriptive analysis, classic assumption test, and path analysis.The results of this research indicate that Corporate Social Responsibility has significant affects on profitability, Intellectual Capital has no significant affect on profitability, Corporate Social Responsibility has significant affect on the firm value, Intellectual Capital has no significant affect on the firm value, profitability has significant affects on the firm value, Corporate Social Responsibility has significant affects on the firm valuewith profitability as an intervening variable, and Intellectual Capital has no significant affects on the firm value with profitability as an intervening variable.